End‐stage kidney disease patients from ethnic minorities and mortality in coronavirus disease 2019. Issue 1 (10th August 2021) - Tabinor, Matthew; Crowley, Lisa Emma; Godlee, Alexandra; Flanagan, Daisy; Rashid, Raja Muhammad; Baharani, Jyoti; Ferro, Charles Joseph; Eddington, Helen
Abstract: Introduction: Coronavirus disease 2019 (COVID‐19) adversely affects patients who are older, multimorbid, and from Black, Asian or minority ethnicities (BAME). We assessed whether being from BAME is independently associated with mortality in end‐stage kidney disease (ESKD) patients with COVID‐19. Methods: Prospective observational study in a single UK renal center. A study was conducted between March 10, 2020 and April 30, 2020. Demographics, socioeconomic deprivation (index of multiple deprivation), co‐morbidities (Charlson comorbidity index [CCI]), and frailty data (clinical frailty score) were collected. The primary outcome was all‐cause mortality. Data were censored on the 1st June 2020. Findings: Overall, 191 of our 3379 ESKD patients contracted COVID‐19 in the 8‐week observation period; 84% hemodialysis, 5% peritoneal dialysis, and 11% kidney transplant recipients (KTR). Of these, 57% were male and 67% were from BAME groups (43% Asian, 17% Black, 2% mixed race, and 5% other). Mean CCI was 7.45 (SD 2.11) and 3.90 (SD 2.10) for dialysis patients and KTR, respectively. In our cohort, 60% of patients lived in areas classified as being in the most deprived 20% in the United Kingdom, and of these, 77% of patients were from BAME groups. The case fatality rate was 29%. Multivariable cox regression demonstrated that BAME (hazard ratio [HR]: 2.37, 95% CI: 1.22–4.61) was associated with all‐cause mortality after adjustment for age, deprivation, co‐morbidities, and frailty. Associations with all‐cause mortality persisted in sensitivity analyses in patients from South Asian (HR: 2.52, 95% CI: 1.24–5.12) and Black (HR: 2.43, 95% CI: 1.04–5.67) ethnic backgrounds. Discussion: BAME ESKD patients with COVID‐19 are just over twice as likely to die compared to White patients, despite adjustment for age, deprivation, comorbidity, and frailty. This study highlights the need to develop strategies to improve BAME patient outcomes in future outbreaks of COVID‐19.